(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The theoretical assumptions of Behavior Analysis and the empirical literature have both linked tolerance to reinforcer delay to self-control. However, a developmental perspective about its relevance has not yet been explored. The present study analyzed the tolerance to reinforcer delay as a possible behavioral cusp precursor to self-control. For this analysis we used texts by Skinner and other behavior analysts that discuss the constructs of self-control, human development and behavioral cusp, as well as empirical articles examining the relationships between tolerance to reinforcer delay and self-control. In addition, developmental contingencies, which may favor the tolerance to reinforce delay were discussed. It is concluded that the tolerance to reinforcer delay meets all criteria established to be considered a behavioral cusp and that, in this sense, should constitute an important target of intervention in childhood, aiming at the future development of self-control.